Clinical Evaluation of Three Types of CAD/CAM Inlay/Onlay Materials After 1-Year Clinical Follow Up - (:unkn) unknown (DENNIS BARBER LTD, 2019)
Objective: To evaluate the clinical performance and the marginal adaptation of inlay/ onlay restorations made of lithium of a new lithium disilicate strengthened, lithium alumino-silicate glass-ceramic (LAS) material compared with a conventional lithium-disilicate glass-ceramic (LDS) and new-generation polymer-based CAD/CAM resin composite (CS) materials over one year. Materials and methods: Seventy-five inlay-onlay restorations were placed in 35 patients. The restorations were assigned and randomized to three groups as LDS, LAS, and CS. Clinical evaluations were performed after one week, six months, and one year after the cementation, according to the modified United States Public Health Services (USPHS) criteria. The marginal quality analyses of 21 samples (n=7) were assessed under a scanning electron microscope. The data were analyzed by using Friedman, Wilcoxon Signed Ranks, Chi-square and Paired t-tests (p<0.05). Results: No statistically significant difference (p>0.05) was found between groups in the modified USPHS, gingival index, and plaque index evaluations, and the total success rate was 100% for three groups after one year. Following SEM evaluations in all groups, continuous margin percentages were decreased, but these results were not statistically significant (p>0.05). Conclusions: Lithium disilicate-strengthened lithium aluminosilicate glass-ceramics can be considered a reliable material for an option for posterior onlay/inlay restorations.
Keywords: SEM; Clinical Evaluation; CAD/CAM; Lithium Disilicate Ceramics; CAD CAM Resin Composite; GLASS-CERAMIC INLAYS; MECHANICAL-PROPERTIES; INDIRECT-COMPOSITE; 2 SYSTEMS; ONLAYS; RESTORATIONS; PERFORMANCE; ADAPTATION; RESISTANCE; TEETH